2014
DOI: 10.11604/pamj.2014.19.157.4916
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculose ganglionnaire: aspects épidémiologiques, diagnostiques et thérapeutiques, à propos de 357 cas

Abstract: La tuberculose ganglionnaire (TG) est la localisation extrapulmonaire la plus fréquente au Maroc. Elle pose encore un problème diagnostique et thérapeutique. Le but du travail est d’ étudier le profil épidémiologique, diagnostique et thérapeutique de la tuberculose ganglionnaire. Il s'agit d'une étude rétrospective portant sur les nouveaux cas de TG suivis au centre spécialisé de tuberculose de Marrakech, entre Janvier 2011 et Décembre 2012. Trois cents cinquante sept cas de TG ont été inclus sur l'ensemble de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
7
5
0
Order By: Relevance
“…The lymphadenopathies involved mostly the transversal cervical chain (55.8%), spinal chain (50%), and jugulocarotidian chain (32.4%). These results are similar to those of the literature, which reported the LNTB mostly to be localized to the anterior or posterior cervical chains (70-90%) [7,12,18]. The LNTB is often bilateral, and noncontiguous lymph nodes can also be involved [3].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lymphadenopathies involved mostly the transversal cervical chain (55.8%), spinal chain (50%), and jugulocarotidian chain (32.4%). These results are similar to those of the literature, which reported the LNTB mostly to be localized to the anterior or posterior cervical chains (70-90%) [7,12,18]. The LNTB is often bilateral, and noncontiguous lymph nodes can also be involved [3].…”
Section: Discussionsupporting
confidence: 91%
“…Although no particular underlying diseases were found in 38 cases (55.9%), 6 patients (8.8%) had diabetes and 12 patients (17.7%) were HIV positive. Similarly, Hamzaou et al [18] reported 9% and 3.6% cases of diabetes and HIV infection, respectively. Also, Benjelloun et al [19] reported 1 patient to have diabetes.…”
Section: Discussionmentioning
confidence: 85%
“…With respect to the topography, cervical lymph nodes were the most frequent in our series (86%). This tendency was also reported by various other authors [ 5 , 17 , 18 ]. This could be explained by the anatomical position and physiological role of the jugular-carotid lymph node chain being more accessible compared to the respiratory tract.…”
Section: Discussionsupporting
confidence: 89%
“…Among the EMR countries, Tunisia has the highest proportion of EPT cases (60%) [1]. In Morocco, EPT accounts for 46% of all TB cases, with lymph node EPT being the most common localization followed by pleural EPT [1,7,10]. Due to the paucibacillary nature of the non-respiratory specimens, diagnosis of EPT remains challenging.…”
Section: Introductionmentioning
confidence: 99%